An active simulator for neonatal intubation: Design, development and assessment. (January 2017) - Baldoli, Ilaria; Tognarelli, Selene; Vangi, Ferdinando; Panizza, Davide; Scaramuzzo, Rosa T.; Cuttano, Armando; Laschi, Cecilia; Menciassi, Arianna
Highlights: Neonatal intubation is a delicate procedure requiring adequate training. A commercial skill trainer was instrumented to provide feedback during simulation. FSRs and a textile pressure sensor were employed to measure forces on critical points. Tests were performed with clinicians to evaluate the device's performances. Data recorded during trials give highlights that are useful for the training outcome. Abstract: This study describes the technical realization and the pre-clinical validation of a instrumented neonatal intubation skill trainer able to provide objective feedback for the improvement of clinical competences required for such a delicate procedure. The Laerdal ® Neonatal Intubation Trainer was modified by applying pressure sensors on areas that are mainly subject to stress and potential injuries. Punctual Force Sensing Resistors (FSRs) were characterized and fixed on the external side of the airway structure on the dental arches and epiglottis. A custom silicone tongue was designed and developed to integrate a matrix textile sensor for mapping the pressure applied on its whole surface. The assessment of the developed tool was performed by nine clinical experts who were asked to practice three intubation procedures apiece. Median and maximum forces, over threshold events (i.e. 2 N for gingival arch sensors and 7 N for epiglottis and tongue sensors respectively) and execution time were measured for each trainee. Data analysis from training sessions revealed that the epiglottis is the point mainly stressed during an intubation procedure (maximum value: 16.69 N, median value: 3.11 N), while the analysis carried out on the pressure distribution on the instrumented tongue provided information on both force values and distribution, according to clinicians' performance. The debriefing phase was used to enhance the clinicians' awareness of applied force and gestures performed, confirming that the present study is an adequate starting point for achieving and optimizing neonatal intubation skills for both residents and expert clinicians.